La circulation sur la route transcanadienne dans l’Ontario central - Hamelin, Louis-Edmond (Cahiers de géographie du Québec, 1965)
This study concerns the section of the trans-Shield route between Lake Simcoe and the boundary of Manitoba. The data were obtained from the Ontario Department of Highways for the period from 1958 to January 1965 and by personalinquiry carried out in May 1965. To what extent does this section link the two principal cores of the Canadian ecumene, that is, the Lower Great Lakes - St. Lawrence area and southern Alsama ?After having briefly presented the geographic environment in which the route is situated, the author presents a number of statistics. The annual average daily traffic outside the towns is light : 3,000 vehicles in the more popular sectors and less than 1,000 in the less frequented parts. There is a decrease in the intensity of traffic from east to west as jar as Dryden. For the entire 1,200 miles of highway, three fourths of the vehicles have Ontario license plates. East of Sault St. Marie, the vehicles from outside Ontario come mainly from the U.S.A. whereas in the Kenora area they are principally from Manitoba. Traffic is three to Jour times heavier in summer than in winter. In the winter season the number of non-Ontario cars is very small and there are relatively more trucks than in summer. In the month of May the situation is more similar to that in winter than to that in summer. In the last jive years the frequentation of the route bas greatly increased ; at Dinorwic the number of vehicles in July bas multiplied five times. From a regional point of view, three sectors should be recognized : (1) from Lake Simcoe to Sault St. Marie, (2) from Sault St. Marie to Dryden, and (3) extreme western Ontario. Economically, the Ontario section of the Trans-Canada Highway is not a profitable enterprise. Furthermore, this route appears to be much less transcontinental than the parallel rail line. In several ways the trans-Shield corridor presents a greater obstacle to the continuity of the Canadian population ecumene than the Rocky Mountains, or even the Appalachian barrier. Nevertheless, central Ontario is a part of the ecumene but it is only an « ecumene of liaison » with low intensity of occupance. An office of Trans-Canadian traffic should be created.